Efektivitas Penggunaan Media Visual dalam Pembelajaran Bahasa Inggris di Sekolah Menengah Pertama - Hanifah Diah Indriyaningrum; Muth-Hir Qolby Tobba; Lunna Wuryandari (BADAN PENERBIT STIEPARI PRESS, 2022)
The aims of the study were to determine: 1) Utilization of ZIS at BMH Denpasar Bali. 2) The pilot program for spreading da'i to build the country at BMH Denpasar Bali. 3) Obstacles faced by BMH Denpasar Bali in the utilization of ZIS through the pilot program for spreading da'i to build the country. This research method is descriptive-qualitative. The informants were 6 people who were selected purposively. Collecting data through observation, interviews, and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. Based on the results of the study, it shows that in the utilization of ZIS in Baitul Maal Hidayatullah (BMH) Denpasar Bali, there are 3 values, namely: allocation, target and distribution. As for the program to spread da'i to build the country, it has 3 values, namely: social, education and da'wah. The inhibiting factors in the utilization of ZIS through the pilot program for spreading da'i are: the decline in ZIS funds due to the COVID-19 pandemic, the lack of good human resources in Baitul Maal Hidayatullah (BMH) Denpasar Bali and the lack of human resources in the cottage as educators, a friendly environment. still predominantly Hindu community so that the education process through this program is less than optimal, far from urban centers making it difficult for health services and the lack of facilities and infrastructure in the cottage.